Matriclans shape populations: Insights from the Angolan Namib Desert into the maternal genetic history of southern Africa. Issue 3 (3rd January 2018) - Oliveira, Sandra; Fehn, Anne‐Maria; Aço, Teresa; Lages, Fernanda; Gayà‐Vidal, Magdalena; Pakendorf, Brigitte; Stoneking, Mark; Rocha, Jorge
Abstract: Objectives: Southern Angola is a poorly studied region, inhabited by populations that have been associated with different migratory movements into southern Africa. Apart from Kx'a‐speaking San foragers and Bantu‐speaking pastoralists, ethnographic and linguistic studies have suggested the existence of an enigmatic array of pre‐Bantu communities, like the Kwepe (formerly Khoe‐Kwadi speakers), Twa and Kwisi. Here, we evaluate previous peopling hypotheses by assessing the relationships between different southern Angolan populations, based on newly collected linguistic data and complete mtDNA genomes. Materials and methods: We analyzed 295 complete mtDNA genomes and linguistic data from seven groups from the Namib Desert (Himba, Kuvale, Tjimba, Twa, Kwisi, Kwepe) and Kunene Province (!Xun), placing special emphasis on the evaluation of the genealogical consistency of the matriclanic system that characterizes most of these groups. Results: We found that the maternal genetic structure of all groups from the Namib Desert was strongly shaped by the consistency of their matriclanic system. The tracking of the maternal heritage enhanced population differentiation by genetic drift and is likely to have caused the divergent mtDNA profiles of the Kwepe, Twa, and Kwisi, who probably formed a single population within the spectrum of Bantu genetic variation. Model‐based analyses further suggest that the dominant pastoral groups Kuvale and Himba may be grouped into a Bantu proto‐population which also included the ancestors of present‐day Tjimba and Herero, as well as the Khoe‐Kwadi speaking Damara foragers from Namibia. Discussion: The view from southwestern Angola offers a new perspective on the populating history of southern Africa and the Bantu expansions by showing that social stratification and different subsistence patterns are not always indicative of remnant groups, but may reflect Bantu‐internal variation and ethnogenesis.